Analysis of additional regulators necessary for autophagy in Drosophila muscle tissue - Guo, Yungui (My University, 2024)
Our lab uses Drosophila as a model organism to study the role of Bcl-2-associated athanogene 3 (BAG3)-mediated chaperone-assisted selective autophagy (CASA) in skeletal muscle. We previously showed that the serine/threonine protein kinase (NUAK) biochemically and genetically interacts with Drosophila Starvin (Stv), the ortholog of mammalian BAG3. While this NUAK-Stv complex plays a role in the autophagic clearance of proteins, the discovery of novel autophagy regulators will facilitate a better understanding of tissue and/or stress-specific responses. To this end, we have employed a sensitized genetic assay using an RNA interference (RNAi) approach and found NUAK and stv genetically interacts with genes that encode for Striatin- interacting phosphatase and kinase (STRIPAK) complex proteins, including Striatin-interacting protein (Strip), MOB kinase activator 4 (Mob4), and Connector of kinase to AP-1 (Cka). These data indicate that both NUAK and stv function in the same biological process with genes that encode for STRIPAK complex proteins. To confirm these results biochemically, we performed affinity purification-mass spectrometry (AP-MS) with Strip as a bait protein. Indeed, we found that STRIPAK complex members can be co-purified from Drosophila larval muscle tissue with Stv and NUAK. Knockdown of Strip in muscle tissue using RNAi resulted in the buildup of ubiquitinated cargo, p62, and Autophagy-related 8a (Atg8a), indicating alternations in the autophagy pathway. In fact, autophagic flux was reduced in muscles with Strip RNAi, but lysosome biogenesis and activity remained unchanged. Our findings suggest a model in which the STRIPAK-NUAK-Stv complex collaboratively regulates autophagy in muscle tissue. We also utilized p62 immunostaining to test microtubule-related candidates as another approach to further our understanding of autophagy regulation in muscle tissue. Pavarotti (Pav)/kinesin family member 23 (KIF23) emerged as one of the strongest candidates using this approach. Pav and its binding partner Tumbleweed (Tum)/RacGAP1 are well known for their role in MT-dependent movements during cytokinesis. We found that Ubiquitin and p62 are recruited to damaged mitochondria and formed autophagosome clusters with Atg8a upon muscle-specific RNAi knockdown of Pav or Tum in larval muscles. This Pav-Tum complex is also enriched in the nucleus, counterintuitive for a direct role in MT-mediated transport throughout the muscle cell. However, these observations are consistent with a recent report describing the roles of Pav and Tum in nuclear envelope budding (NEB), an alternative pathway for the export of cargo that is too big to traverse through nuclear pores. In Drosophila larval muscles, mRNAs necessary for mitochondrial integrity, such as Marf mRNA, is one of the cargos of the NEB pathway. As expected, Marf mRNA levels were reduced in the myoplasm of pav RNAi or tum RNAi muscles. We also observed that the knockdown of Marf or other NEB components, such as Wash or Torsin, resulted in autophagosome clustering. Together, these findings suggest a model in which blocking NEB decreases mitochondrial activity, subsequently leading to the recruitment of p62 and autophagosome components for lysosomal degradation. Our research demonstrated that the STRIPAK complex collaborates with the NUAK-Stv complex in the autophagic clearance of proteins. This finding enhances our understanding of the BAG3-mediated CASA in protein quality control. Additionally, we are the first group to report abnormal mitophagy resulting from defects in NEB formation. Autophagosome clusters represent a unique phenotype that can be readily examined through immunostaining and microscopy techniques. Consequently, we propose that our research provides a rapid and straightforward method for detecting defects in NEB development.
Keywords: Autophagy; Drosophila muscle; Mitophagy; Nuclear envelope budding; Strip; Mitochondria